Application of QSPM and SWOT Model in Formulating Housing Supply Strategy for the Deprived - Hamid Reza Mohammadi; mohsen pakparvar (تحقیقات کاربردی علوم جغرافیایی)
In relation to the housing of the disadvantaged, the possibility of access to a suitable housing for every Iranian household in accordance with the household's needs in such a way that the housing concern does not exceed other areas of the household's life and stable and safe access to the household's housing is also guaranteed, showing the ideal vision of the housing sector in documentary studies, is related to disadvantaged groups. The purpose of this study is to achieve the set of strategies and the general form of realistic and effective programs in the field of housing support for the deprived and low-income groups, which, while determining the limits and type of government intervention in relation to housing and different economic groups, will make the target groups enjoy support programs faster. This study is based on the combined model of SWOT strategic analysis and QSPM strategic planning model and examines the findings of studies and the results of interviews with experts in the field of geography and urban planning. SWOT analysis showed that 1- Ignoring the lack of simultaneous use of the process of management and operation of low-income housing based on the participation of local social institutions and non-governmental organizations 2- Lack of necessary knowledge or disregard for the diversity of needs of the deprived and disregard for Special Characteristics of Target Groups 3. The imbalance between the benefits of different individuals in different groups in relation to support programs has led to the inefficiency of the policies of the deprived and the enjoyment of supportive housing for this group. "Empowerment programs" and "Attracting participation by exploiting local capacity and internal capacities by developing and diversifying empowerment", along with a general balancing policy to increase capacity in non-governmental sectors based on household participation. Faster households have support programs Provides housing and participation of all stakeholders in planning. Keywords: development programs, government policies, housing for the deprived, SWOT analysis, QSPM model.